Sistem Pendukung Keputusan Rekomendasi Lokasi Wisuda Menggunakan Metode MOORA - Rahardjo, Mochamad Dedy Subekti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
In a university, mistakes often occur in choosing a good graduation location, therefore before holding a graduation ceremony at Budi Darma University, you must first determine where the right location is to hold the event, because determining the right location will minimize costs. Graduation is a ceremony of confirmation or inauguration for a student who has completed his education at a university or college. In this research, the aim is to build a decision support system (DSS). Which has a function as a tool to determine decision making in the process of selecting the location for the graduation ceremony to be held by Budi Darma University. Determination of the location of the graduation ceremony is also carried out with great attention to several aspects which are an important strategy that will be considered in determining the location of the graduation ceremony which is absolutely and very much needed. The Moora method is one of the Multi-Criteria decision making (MCMD). Is a method that requires statistical procedures for selecting the best alternative given. This method also produces a very suitable alternative by considering something good and profitable.